c - Anwara Syed Haq (Ḍhaka : Anyaprokash, 2001)
Short stories based on 1971 independence war of Bangladesh.
Short stories.
In Bengali.
Keywords: Short stories, Bengali -- Bangladesh; Bangladesh -- History -- Revolution, 1971 -- Fiction